Potentials of arts education initiatives for promoting emotional wellbeing of Chinese university students - Guo, Yanan (Frontiers in Psychology, 2024)
The present study explores the intricate dynamics influencing the self-efficacy of Chinese university students through the interplay of participation in artistic activities, positive psychological capital, and emotional intelligence. In the context of technological advancements and various challenges post pandemic, this study delves into the multifaceted aspects of university life, where arts education plays a pivotal role in addressing students emotional needs. By integrating emotional intelligence with self-efficacy, this study underscores the positive impact of artistic engagement on self-efficacy, while emphasising on the transformative power of these pursuits. Also, this study establishes that the optimism and resilience contribute to this relationship by considering the mediating role of positive psychological capital. The moderating influence of emotional intelligence in the complex dynamics between arts education and positive psychological capital is another concern, thereby emphasizing the nuanced role of emotional intelligence. With a structured set of questions that were administered to 673 participants with 93.61% recovery rate, this study performs the Cronbach’s alpha test, validation factor, and several related tests in SPSS Statistics 29.0, bootstrap, and AMOS 25.0 software. Current results shows the importance of a holistic approach in Chinese institutions. With a focus on promoting artistic engagement to enhance students' self-efficacy, this study determines the profound impact of arts education on students' overall well-being and educational experience. In conclusion, this research highlights the constructive impact of artistic engagement on the self-efficacy of Chinese university students. Chinese institutions should encourage a varied range of artistic engagements as a response to the contemporary challenges confronted by their students.